THE IMPLEMENTATION OF CORE LEARNING MODEL IN WORK AND ENERGY TOPIC FOR SENIOR HIGH SCHOOL’S STUDENT - INDRIATI, PALUPI; SUNARTI, TITIN (Inovasi Pendidikan Fisika, 2019)
This research aims to describe the result of implementation CORE model in work and energy topic for senior high school?s student. The type of this research is pre-experimental with one group pretest-posttest design. This research use one experiment class and two replication classes. Instrument used in this research is observation sheet of learning implementation. The implementation of the CORE model is observed by the observer through the scoring on the observation sheet of learning implementation. The implementation of learning with CORE model is very good at the first and second meeting in all classes. The implementation of syntax is shown by the average high score with category very good at the first meeting which is 3.51 and the second meeting is 3.61.Keywords: CORE Model, Implementation, Learning Activities